(untitled) (Scientific journal of the Fergana State University, 2023)
The article reveals the key requisites of the ascertaining experiment to identify the level of self-educational activity of students of medical universities in relation to the learning process and specifically in the study of the English language. The substantiation and application of self-education criteria are given, the shortcomings and difficulties are described, and the ways of improving management and effective methodological support of students’ independent work are outlined.